Rediscovering, Reevaluating, and Restoring Lost River-Wetland Corridors - Wohl, Ellen; Castro, Janine; Cluer, Brian; Merritts, Dorothy; Powers, Paul; Staab, Brian; Thorne, Colin (Frontiers in Earth Science, 2021)
River-wetland corridors form where a high degree of connectivity between the surface (rheic) and subsurface (hyporheic) components of streamflow creates an interconnected system of channels, wetlands, ponds, and lakes. River-wetland corridors occur where the valley floor is sufficiently wide to accommodate a laterally unconfined river planform that may feature morphologically complex, multi-threaded channels with vegetated bars, islands, and floodplains. River-wetland corridors can develop anywhere there is valley expansion along a drainage network, from the headwaters to estuaries or deltas, and they are found across all latitudes and within all biomes and hydroclimates. River-wetland corridors may be longitudinally continuous but are commonly interspersed with single-thread reaches in narrower portions of the valley. The development and persistence of river-wetland corridors is driven by combinations of geologic, biotic, and geomorphic processes that create a river environment that is diverse, heterogeneous, patchy, and dynamically stable, and within which patterns of flow, sediment features, and habitats shift continually. Hence, we describe these polydimensional river corridors as “kaleidoscope rivers.” Historically, river-wetland corridors were pervasive in wide, alluvial valley reaches, but their presence has been so diminished worldwide (due to a diverse range of anthropogenic activities and impacts) that the general public and even most river managers are unaware of their former pervasiveness. Here, we define river-wetland corridors as a river type; review paleoenvironmental and historical records to establish their past ubiquity; describe the geologic, biotic, and geomorphic processes responsible for their formation and persistence; and provide examples of river-wetland corridor remnants that still survive. We close by highlighting the significance of the diverse river functions supported by river-wetland corridors, the consequences of diminution and neglect of this river type, and the implications for river restoration.